SOCIOCULTURAL DIMENSIONS OF SPOKEN LANGUAGE USE IN EDUCATIONAL CONTEXTS: A MICRO-ETHNOGRAPHIC ANALYSIS - Iwan Jazadi (GLOBAL: Education Language and Humanity Journal, 2024)
This study explores the sociocultural dimensions of spoken language use in educational contexts through a micro-ethnographic analysis of three naturally occurring speech events in a tertiary institution. Grounded in sociocultural discourse analysis and systemic functional linguistics, the research examines how cultural norms, institutional expectations, and power relations shape classroom talk. Data were collected via unobtrusive naturalistic observation and analyzed using frameworks by Mercer and Halliday to interpret the interplay between linguistic form and social function. Findings reveal that indirectness, pragmatic misalignment, and minimalist engagement reflect speakers’ cultural backgrounds, identity negotiations, and stages of language acquisition. The study underscores spoken discourse as a vehicle for enacting identity, asserting agency, and navigating institutional hierarchies, particularly in multicultural and multilingual settings. Pedagogical implications include the need for enhanced pragmatic instruction, awareness of discourse asymmetries, and inclusive communication strategies in language education. This work contributes to our understanding of how spoken interactions function as sociocultural acts within educational environments